Foreword to: Indiana University's Response to the Addictions Crisis: A Grand Challenge Initiative - Robin Newhouse PhD, RN, FAAN (SAGE Publishing, 2024)
Use of heroin, prescription painkillers, methamphetamines, and fentanyl led to a national health crisis in 2017, resulting in 1852 overdose deaths in Indiana. Governor Eric J. Holcomb made tackling substance use in the state one of his highest priorities, calling on all Hoosiers to collaborate. In October 2017, Indiana University (IU) President Michael A. McRobbie responded, announcing that the University would be initiating the Responding to the Addictions Crisis Grand Challenge (AGC). Partners included Governor Holcomb, IU Health, and Eskenazi Health. Leveraging the university's research strengths and partnering with more than 160 community organizations across the state, the AGC sought to address substance use facing Indiana and beyond. Fifty interdisciplinary research projects were created through the AGC, focusing on IU's greatest strength in five areas: (1) education, training, and certification; (2) data science and analysis; (3) policy analysis, economics, and law; (4) basic, applied, and translational research; (5) community engagement and workforce development. Diversity, equity, and inclusion implications were often considered. This supplement describes the IU approach to address the health of the people of the State, investigator initiated projects and research conducted to inform practice, strategy and policy.